Synthesis of furans using biosynthesized Ag nanostructures as a highly effective and easily retrievable catalyst - Yasir Waleed Abdulhameed; Hossein Shahbazi-Alavi; Baram Ahmed Hamah Ameen (Nanochemistry Research, 2023)
Nano-Ag as a green heterogeneous catalyst was utilized for the synthesis of furans by the three-component reaction of phenylglyoxal, dimethyl acetylenedicarboxylate, and primary amines. The best results were obtained in the presence of 4 mol% of nano-Ag in CH2Cl2 at room temperature. The nanocatalyst was characterized by UV-VIS, FT-IR, XRD, SEM and EDS. Ag nanostructures were prepared using extract of Echium amoenum. Some of the substantial features of this method include experimental simplicity, wide range of products, excellent yields in short reaction times, reusability of the catalyst, and low catalyst loading.